Anthropogenic short-lived halogens increase human exposure to mercury contamination due to enhanced mercury oxidation over continents - Fu, Xiao (2024)
Mercury (Hg) is a contaminant of global concern, and an accurate understanding of its atmospheric fate is needed to assess its risks to humans and ecosystem health. Atmospheric oxidation of Hg is key to the deposition of this toxic metal to the Earth’s surface. Short-lived halogens (SLHs) can provide halogen radicals to directly oxidize Hg and perturb the budget of other Hg oxidants (e.g., OH and O3). In addition to known ocean emissions of halogens, recent observational evidence has revealed abundant anthropogenic emissions of SLHs over continental areas. However, the impacts of anthropogenic SLHs emissions on the atmospheric fate of Hg and human exposure to Hg contamination remain unknown. Here, we show that the inclusion of anthropogenic SLHs substantially increased local Hg oxidation and, consequently, deposition in/near Hg continental source regions by up to 20%, thereby decreasing Hg export from source regions to clean environments. Our modeling results indicated that the inclusion of anthropogenic SLHs can lead to higher Hg exposure in/near Hg source regions than estimated in previous assessments, e.g., with increases of 8.7% and 7.5% in China and India, respectively, consequently leading to higher Hg-related human health risks. These results highlight the urgent need for policymakers to reduce local Hg and SLHs emissions. We conclude that the substantial impacts of anthropogenic SLHs emissions should be included in model assessments of the Hg budget and associated health risks at local and global scales.